Incidencia de ansiedad en el ámbito académico en un adolescente de 17 años de edad del Cantón Montalvo - Murrieta López, Allison Leslie (2023)
The theme of this case study is “Incidence of anxiety in the academic field in a 17-year-old adolescent from the Canton of Montalvo”, and has the research line of the career: educational, supported by the research subline of the psychology career: learning and behavioral problems in educational contexts, since the anxiety variable is related to the academic variable, the work is supported by a descriptive-inductive method supported by the mixed approach. The psychometric techniques used will be: Beck anxiety inventory, Hamilton anxiety scale, these will be applied to the student, the survey is structured by 6 questions, it is applied to the teacher, these work tools allow the researcher to determine that the study subject presents a moderate level of anxiety, after this the psychotherapeutic plan that the patient must follow is proposed.